Study on the impact of industrial flue gases on the PCDD/Fs congener profile in ambient air - Węgiel, Małgorzata; Chrząszcz, Ryszard; Maślanka, Anna; Grochowalski, Adam (Chemosphere (Oxford), 2014)
•We examined the impact of combustion processes on the PCDD/F profile in ambient air.•We determined seventeen PCDD/F congeners in flue gas and ambient air samples.•PCDD distribution in flue gas samples is similar regardless of emission source.•PCDD profiles in ambient air are parallel and related to those in flue gas samples.•PCDF distribution in ambient air depends on the site of sampling and flue gas emitter. The aim of this study was to examine the impact of emissions from combustion processes from sinter, medical, waste and sewage waste incineration plants on the PCDD and PCDF congener profile in ambient air in Krakow (city in Poland). The subject matter of the study were air samples from the outskirts and the city center. It was found that in flue gases from industrial sources and in ambient air the share of PCDF congeners in relation to the total content of PCDD/Fs was higher than the share of PCDDs. However, in air samples collected in the city center, this relationship was reversed. The PCDD congener profiles in flue gases and in air samples are comparable. However, in the samples from the city centre, the share of OCDD is significantly higher and amounts to about 80%. The PCDF congener shares show higher spatial diversity, although in all the analyzed air samples, ODCF and 1,2,3,4,6,7,8 HpCDF dominated. Analyzing the share of congeners in regard to the sum of PCDDs/Fs a mutual resemblance of air from the suburbs, exhaust gases from the sinter ore and sewage sludge incinerator plant was observed. The study showed a similarity between the profile of congeners in air from the city centre and exhaust gases from the medical waste incinerator.